AB0395 One Year Retrospective Analysis of Side Effects of Non-Biologic Disease Modifying Anti-Rheumatic Drugs. (15th July 2016) - Maddox, N.L.; Gut, C.I.; Bhatt, R.; Moore, O.A.
Abstract : Background: Non-biologic disease modifying anti-rheumatic drugs (nbDMARDs) (e.g. Methotrexate (MTX), Sulfasalazine (SUZ) and Leflunomide (LEF)) are used as initial treatment for autoimmune conditions; such as rheumatoid arthritis and psoriatic arthritis. However, there is limited evidence upon the proportion of patients who have to stop medication due to side-effects. Infoflex (CIMS) is an electronic system implemented at Derriford Hospital, May 2014. This system was used to record Rheumatology drugs started and stopped and causes for drug cessation 1 . Objectives: Our aim was to determine the proportion of patients who had to stop taking nbDMARDs due to adverse events (AE) or side-effects (SE), document the commonest reactions and examine whether there were gender differences in drug cessation. Methods: A retrospective search was performed using Infoflex for all Rheumatology patients at Derriford Hospital for patients who had been started on nbDMARDs for a one year period between 01/12/2014–30/11/2015. Patients were selected for inclusion if they were continuing on the drug or had stopped it due to AE or SE. Patients were excluded if they had stopped their drug due to inefficacy. Results: 1424 patient records were documented from a total of 1080 patients that met the inclusion criteria. Patients included were treated for a variety of rheumatological conditions with the following nbDMARDs; MTX (n=588), Hydroxychloroquine (HCQ) (n=385), SUZ (n=303), LEF (n=92), Azathioprine (AZA) (n=29), Mycophenolate Mofetil (MMF) (n=21), Cyclophosphamide (n=2), Gold (n=2), Cyclosporine (n=1), Tacrolimus (n=1). The percentage and number of patient records that ceased medication due to AE or SE was; MTX 13.44% (n=79), HCQ 13.25% (n=51), SUZ 31.68% (n=96), LEF 20.65% (n=19), AZA 31.03% (n=9), MMF 9.5% (n=2). The nbDMARD dosage did not have any relationship to the rate of SE or AE. Mean length of usage for each drug before stopping due to AE or SE was: MTX (95.9 days), HCQ (57.2 days), SUZ (57.1 days), LEF (68.2 days), AZA (69.8 days), MMF (175.5 days). The most common AE or SE was found to be gastrointestinal for all drugs, except MMF. The female to male ratio for those who discontinued MTX, HCQ and SUZ was increased in comparison with the female to male ratio for overall drug usage. Conclusions: SUZ had the highest percentage of patients stopping medication (31.68%) with the shortest duration of usage (57.1 days). MMF had the lowest percentage of patients stopping medication (9.5%) with the longest duration of usage (175.5 days). The commonest reported AE or SE for all drugs (except MMF) were within the gastrointestinal category; principally gastrointestinal intolerance and nausea. The strengths of our data lie in the amount of information captured and its real world setting. Its weakness is the characterisation of SE is insufficiently specific and we have been unable to classify by disease. Future data collection is required to fully capture the patients who will discontinue nbDMARDs within the current study population. However, these data could potentially aid clinicians in advising rheumatology patients of the potential risks of different nbDMARDs. References: Chameleon Information Management Services Ltd (CIMS). http://www.infoflex-cims.co.uk/cims/news/2015/11/plymouth_rheumatology /p> Acknowledgement: We are very grateful for the work of all staff and the help from all patients in our Rheumatology department Disclosure of Interest: None declared